The impact of vaccination on the burden of invasive pneumococcal disease from a nationwide surveillance program in Lebanon: an unexpected increase in mortality driven by non-vaccine serotypes. (2nd December 2022) - Reslan, Lina; Youssef, Nour; Boutros, Celina F.; Assaf-Casals, Aia; Fayad, Danielle; Khafaja, Sarah; Akl, Fata; Finianos, Marc; Rizk, Amena A.; Shaker, Rouba; Zaghlout, Alissar; Lteif, Mireille; et al.
ABSTRACT: Background: The impact of pneumococcal conjugate vaccines (PCVs) on the burden of invasive pneumococcal disease (IPD) and serotype distribution was examined across age groups from data collected by the Lebanese Inter-Hospital Pneumococcal Surveillance Program. Methods: Between 2005 and 2020, 593 invasive Streptococcus pneumoniae isolates were collected from 79 hospitals throughout Lebanon. Serotypes and antimicrobial resistance (AMR) profiles were identified, and trends compared over 3 eras: PCV7, post-PCV7/ pre-PCV13, and PCV13 eras. Results: The prevalence of PCV7 serotypes decreased significantly from 43.6% in the PCV7 era to 17.8% during the PCV13 era ( p <0.001). PCV13-only serotypes remained stable in the PCV13 compared to the post-PCV7 eras, especially serotypes 1 and 3, whereas non-vaccine types (NVT) increased throughout the study period, especially 24 and 16F. The mortality rate increased substantially from 12.5% (PCV7 era) to 24.8% (PCV13 era). A significant decrease in AMR was observed across the three study eras. Conclusion: PCVs substantially impacted IPD and AMR in vaccinated and unvaccinated populations despite an increase in mortality driven by NVT. Broadening the recommendation of vaccination to include older age-groups, using higher valency vaccines, and implementing stringent antimicrobial stewardship are likely to further impact the burden of IPD.